G-mont Cable Brno - Jussupov, Daniyar (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Cílem bakalářské práce bylo vytvoření jednotlivých stupňů projektové dokumentace – Dokumentace pro stavební povolení a Dokumentace pro provedení stavby na základě studie, zpracované v předmětu AG35. Předmětem vypracování bakalářské práce je novostavba G-mont Cable závodu na výrobů kabelů na ulici Těžební, v městské části Brno-Černovice. Inspirací pro stavbu je typicky kabel černé barvy, který v řezu sestaven s kabelu různých barev: červená, modrá, zelená, žlutá. Objekt je rozdělen na tři celky - výroba, administrativa a sociální zázemí, ale objekt vypadá jako jeden celek. Pro fasádu používán plech černé barvy ks1000. Přes celou stavbu probíhají barevné čáry, v výrobní části to jsou okna, v administrativní části jenom plastové sklo na fasádě. Stavba má dynamický tvar s šikmými čarami na fasádech. V administrativních části je velký střešní světlík. Světlo přicházející do hlavní výroby proniká přes pilové světlíky, orientované na sever. Rozptýlené světlo není agresivní a neruší v žádném denním čase.

The aim of the bachelor thesis was the creation of individual stages of the project documentation - Documentation for Building Permits and Documentation for building construction based on the study, elaborated in subject AG35. The subject of the bachelor's thesis is a new building of the G-mont Cable plant for cable production on the street Těžební, in the Brno-Černovice district. The building's inspiration is typically a black-color cable that has been assembled with a cable of different colors: red, blue, green, yellow. The building is divided into three units -production, administration and social facilities, but the building looks like a whole. For the facade, the black color sheet ks1000 is used. Throughout the construction there are colored lines, in the production part are windows, in the administrative part only plastic glass on the facade. The building has a dynamic shape with sloping lines on the facades. In the administrative part there is a large roof skylight. The light coming into the main production penetrates through the saw blades facing north. Scattered light is not aggressive and does not interfere in any time of day.
G-mont Cable Brno
Keywords: G-mont Cable; Brno-Černovice; výroba; administrative; kabel; G-mont Cable; Brno-Černovice; production; administration; cable